Bosnian society in the period of establishing the Yugoslav revolutionary government (1943-1950) - Katz, Vera (Historical Thought, 2025)
In this paper the author analysed some of the main directions of the constitution of the Communist authorities in Bosnia and Herzegovina in terms of realization of the decisions on the part of the Presidency of AVNOJ and the Central Committee of the Communist Party of Yugoslavia, as well as how their decisions were being implemented in Bosnian society at the time of fully centralized Yugoslav state. On one hand, in some cases it was shown that the Bosnian Communist Party manifested its loyalty to the extreme rigidity and political terror, especially in the matters of dealing with actual and potential "enemies of the people", fearing that the established inter-ethnic consensus might be violated, while the on the other hand one could witness how quickly the state authority was constituted and how effectively all its decisions were implemented in all areas of socio-economic development.